Answer:
i think 300$
Step-by-step explanation:
Answer:
its E.498
Step-by-step explanation: HOPE THIS HELPED....!
Answer:
4x + 1
Step-by-step explanation:
Multiply f + g by x because f + g is in parenthesis:
f(x) + g(x)
Then implement equation #1 for f(x) into our equation:
3x - 1 + g(x)
Then implement the other equation for g(x) into our equation:
3x - 1 + x + 2
Then switch the positions of -1 and +x:
3x + x - 1 + 2
Simmplify:
4x + 1
Pls consider giving my answer the Brainliest! Because it would help and mean a lot! ; )
Answer:
From greatest to least
One and five-sixth rounded to 2
One and StartFraction 7 over 29 rounded to 1
0.16 rounded to 0
Step-by-step explanation:
1+7/29=29+7/29
=36/29
=1.24
Approximately
=1
1+5/6=6+5/6
=11/6
=1.83
Approximately
=2
0.16
Approximately =0
From greatest to least
One and five-sixth rounded to 2
One and StartFraction 7 over 29 rounded to 1
0.16 rounded to 0
Let's use the slope formula!
m = y2 - y1 / (x2 - x1)
m = 6 + 7 / (-3 + 7) = 13/4